Constructing public opinion how politicians & the media mispresent the public - Ericsson, Susan; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2001)
The media regularly use public opinion polls in their reporting of important news stories. But how exactly do they report them and to what end? In this interview, Professor Justin Lewis demonstrates the way in which polling data are themselves used by media to not just reflect what Americans think but instead to construct public opinion itself. The program provides a new way to think about the relationship between politics, media and the public
Title from title screen
This video is based on Justin Lewi's book
Executive producer, Sut Jhally ; camera, Susan Ericsson and Kelly Garner
Presenter: Justin Lewis
Keywords: Public opinion; Public opinion -- United States; Mass media and public opinion -- United States; Political psychology